EFEKTIVITAS PENGGUNAAN METODE INKUIRI TERHADAP PEMAHAMAN KONSEP IPS DAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Saliyah, Saliyah; Mashudi, Mashudi; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is motivated by social studies learning problems that are still teacher-centered, causing students to be passive in learning which results in low understanding of social studies concepts and students' critical thinking skills. The purpose of this study was to determine the effect of the application of metacognisic learning through inquiry methods to increase understanding of social studies concepts and students' critical thinking skills. This study uses a quantitative approach to the quasi experimental method and the design of Non Equivalent Control Group Design. The population in this study. Sampling was done by purposive sampling which resulted in two sample classes. Class VII H as an experimental class that applies learning through inquiry methods while Class VII J is used as a control class that applies inquiry learning methods. The research data obtained by using the test questions instruments understanding the IPS concept in the form of multiple choice questions and test questions of critical thinking skills in the form of the same questions are then analyzed quantitatively. Questionnaire data and observation sheets were analyzed quantitatively descriptive. The results of the study show that learning through inquiry methods can improve understanding of social studies concepts and students' critical thinking skills. But based on statistical calculations with the independent t-test shows that between the experimental class and the control class there were no significant differences.Keywords: effectiveness, inquiry, understanding the social sciences concept, critical thingking